ANALISIS SELISIH TARIF RUMAH SAKIT DENGAN TARIF INACBG’S PASIEN JKN RAWAT INAP KELAS 3 DAN KAITANNTA DENGAN KUALITAS PELAYANAN (Case Study pada RS Betha Medika - Sofian, Suci Rahmawati; Iskandar, Deni; Nurodin, Idang (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
The aim of this study is to analyze differences in hospital rates and INACBG rates on the payment of claims for inpatient JKN class 3 patients and their relation to service quality.Data collected through observation, interviews, and documentation. The study used a descriptive qualitative method.The results of this study indicate that there are differences in hospital real rates with INACBG package rates. Of the 153 cases of disease, there was a positive difference received by the hospital, namely in the case of specialist internal medicine, surgical specialist, pediatric specialist, neurological specialist, and obgyn or midwifery